The Intangibility of Cooperatives as a Competitive Advantage - Ruiz Guerra, Ignacio; Molina Moreno, Valentín (Cooperativismo & Desarrollo, 2014)
The competitive success of companies, according to Navas and Urbina (2002), comes from the identification and management of intangible assets, which has become indispensable for organizations when making a correct assessment of their productive processes. The valuation of productive processes in the field of cooperative management has not remained aloof from this procedure, but nor does it receive the value that it deserves, because the cooperative sector has also failed to value its positioning in the productive realm in which it works and what this leads to. However, the strategies of companies and cooperatives todayrequire a correct and sure knowledge of the intangibility of their own products, and of the effects of their activities in the areas in which they move. Intangible assets are becoming the key to the competitive success of companies, so that their identification, measurement and assessment is a relevant field of study that is now even indispensable for an organization. In this article, the cooperatives in the province of Toledo have been chosen as an example of the potential for the application of strategies for valuation of intangibles, and as a tool for competitive advantage in the context of the opening of new international commercialization channels.
Keywords: cooperatives; intangibility; profitability; values; competitive advantage.